Targeting the Immune System for Pulmonary Inflammation and Cardiovascular Complications in COVID-19 Patients - Colafrancesco, Serena; Scrivo, Rossana; Barbati, Cristiana; Conti, Fabrizio; Priori, Roberta (Frontiers in Immunology, 2020)
In December 2019, following a cluster of pneumonia cases in China caused by a novel coronavirus (CoV), named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the infection disseminated worldwide and on March 11, 2020, the World Health Organization officially declared the pandemic of the relevant disease named coronavirus disease 2019 (COVID-19). In Europe, Italy was the first country facing a true health policy emergency and, as at 6.00 pm on 2 May 2020, there have been more than 209.300 confirmed cases of COVID-19. Due to the increasing number of patients experiencing a severe outcome, global scientific efforts are ongoing to find the most appropriate treatment. The usefulness of specific anti-rheumatic drugs came out as a promising treatment option, together with antiviral drugs, anticoagulants, and symptomatic and respiratory support. For this reason, we feel the duty to share our experience and our knowledge on the use of these drugs in the immune-rheumatologic field, providing in this review the rationale for their use in the COVID-19 pandemic.